Developing Pathways to the Synthesis of Low‐Valence Molybdenum Methoxides: Preparation, Characterization, and Redox Chemistry of Dimeric and Tetrameric Molybdenum Alkoxide Clusters. Issue 4 (8th January 2015) - Kuznetsov, Denis A.; Fedyanin, Ivan V.; Komarova, Natal'ya S.; Shilov, Gennady V.; Martynenko, Vyacheslav M.; Vasil'ev, Sergey G.; Krivenko, Alexander G.; Lyssenko, Konstantin A.; Bazhenova, Tamara A.
Abstract: The rare Mo=Mo double‐bonded dimeric alkoxide complex [Mo2 Cl4 (OCH3 )4 (CH3 OH)2 ] (1 ) was prepared by the simple methanolysis reaction of [MoCl4 (CH3 CN)2 ]. It was shown that the dissolution of1 in thf results in the formation of the [Mo2 O2 Cl4 (OCH3 )2 (thf)2 ] (2 ) and [Mo2 Cl4 (OCH3 )4 (thf)2 ] (3 ) dimers. A novel tetranuclear 10e molybdenum cluster [Mo4 Cl4 O2 (OCH3 )6 (CH3 OH)4 ] (4 ) was synthesized by the spontaneous disproportionation of1 in methanol. An alternative pathway to4 based on the redox reaction of Mo 3+ and Mo 5+ compounds {in the form of [MoCl3 (thf)3 ] and [Mo2 Cl4 (OCH3 )6 ] (5 ), respectively} was proposed and realized. The redox behavior of4 was investigated by means of cyclic voltammetry. It was demonstrated that4 may undergo a reversible two‐electron reduction process, which implies the retention of the Mo4 core, whereas the oxidation is irreversible, proceeding apparently with the destruction of the tetranuclear cluster core. Abstract : A facile synthetic route to the Mo=Mo double‐bonded dimer [Mo2 Cl4 (OCH3 )4 (CH3 OH)2 ] (1 ) and its reactivity are described. The redox‐active cluster [Mo4 Cl4 O2 (OCH3 )6 (CH3 OH)4 ] (4 ) featuring the unique Mo4 core was obtained through two distinct pathways and characterized in the solid state and in solution by numerous techniques.